Factors Related to COVID-19 Prevention Practices of Household Members - Niamun, Areenee; Kasatpibal, Nongyao; Viseskul, Nongkran (Princess of Naradhiwas University Journal, 2025)
This descriptive study aimed to examine COVID-19 preventive practices and the relationships between associated factors and preventive practices. The sample consisted of 402 household members. Data were collected using a questionnaire with content validity indices ranging from 0.96 to 1.00 and reliability coefficients between 0.82 and 0.97. Data were analyzed using descriptive statistics and Spearman’s rank correlation. The results demonstrated that household COVID-19 preventive practices were at a high level. Perceived benefits of prevention and social support were moderately and positively correlated with COVID-19 preventive practices (r =.362 and .453, p < 0.001). Therefore, enhancing household members’ perception of the benefits of prevention, along with providing appropriate support, is essential to promoting effective COVID-19 preventive practices, which can help reduce the risk of transmission within households and communities.